pelatihan Khutbah dan Imam Pelatihan Khutbah dan Imam di Masjid Sabililhuda Boki Owutango, Kelurahan Tamalate, Kecamatan Kota Timur, Gorontalo - Putra, Abdur Rahman Adi Saputera (Komunal Jurnal Pengabdian Masyarakat, 2023)
Abstract This research discusses the implementation of a training program on Friday sermons and the role of imams in Sabililhuda Mosque, Boki Owutango Tamalate, involving 23 participants from various surrounding mosques. The program aims to enhance understanding of religion, religious enthusiasm, and the quality of Friday sermons within the Muslim community. The methods employed in program implementation encompass program planning, execution, post-training activities, program evaluation, collaboration, and community involvement. The results of this program demonstrate improved religious understanding among participants, positive changes in worship practices and Friday sermons, and social impacts encompassing community cohesion, increased social awareness, and community empowerment. The program effectively engaged a substantial number of participants, creating a broader impact that can extend to other mosques within the region. Recommendations include the continuation of the program, training of leaders, further development of training materials, regular evaluations, broader community involvement, and inter-mosque collaboration. This program is a positive step towards strengthening the Muslim community, enhancing religious understanding, religious enthusiasm, and social empowerment. Awareness of the importance of religious education and community empowerment is key to building a better and stronger society. This program marks a positive initial stride in that direction. Penelitian ini membahas pelaksanaan program pelatihan khutbah Jumat dan peran imam di Masjid Sabililhuda Boki Owutango Tamalate, yang melibatkan 23 peserta dari berbagai masjid di sekitarnya. Program ini bertujuan untuk meningkatkan pemahaman agama, semangat keagamaan, dan kualitas khutbah Jumat dalam komunitas Muslim. Metode yang digunakan dalam pelaksanaan program mencakup perencanaan program, pelaksanaan program, kegiatan pascapelatihan, evaluasi program, kolaborasi dan keterlibatan masyarakat. Hasil dari program ini menunjukkan peningkatan pemahaman agama peserta, perubahan positif dalam praktik ibadah dan khutbah Jumat, serta dampak sosial yang mencakup kesatuan komunitas, peningkatan kesadaran sosial, dan pemberdayaan komunitas. Program ini berhasil melibatkan banyak peserta, yang menciptakan dampak yang lebih luas dan dapat menyebar ke masjid-masjid lain dalam wilayah tersebut. Rekomendasi termasuk menjalankan program berkelanjutan, pelatihan kader, pengembangan materi pelatihan, evaluasi rutin, pelibatan masyarakat lebih luas, dan kerjasama antarmasjid. Program ini adalah langkah positif dalam memperkuat komunitas Muslim, meningkatkan pemahaman agama, semangat keagamaan, dan pemberdayaan sosial. Kesadaran akan pentingnya pendidikan keagamaan dan pemberdayaan komunitas Muslim adalah kunci untuk menciptakan masyarakat yang lebih baik dan lebih kuat. Program ini adalah langkah awal yang positif dalam arah itu.